Predicting Cyberbullying Victimization Experiences Based on Family Communication Patterns and Inner Self-Talk in Adolescents - Mousavi, Seyedeh Maryam; Naderlou, Shoukofeh; Nasiri, Farnaz (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: The present study aimed to predict adolescents’ experiences of cyberbullying victimization based on family communication patterns and dimensions of inner self-talk.Methods and Materials: This applied correlational study was conducted among high school students in Shiraz, Iran, during the 2026 academic year. The statistical population consisted of adolescents enrolled in secondary schools, from which 200 participants were selected through convenience sampling. Data were collected using the Cyber Bully/Victim Experience Questionnaire, the Family Communication Patterns Questionnaire, and the Inner Self-Talk Questionnaire. After data collection, the responses were analyzed using SPSS version 26. Pearson correlation coefficients were employed to examine relationships among variables, and multiple regression analysis was conducted to determine the predictive power of family communication patterns and inner self-talk dimensions in explaining cyberbullying victimization experiences.Findings: The results of the multiple regression analysis indicated that the combined dimensions of inner self-talk and family communication patterns explained 31.5% of the variance in cyberbullying victimization experiences. Social assessment emerged as a significant negative predictor of cyberbullying victimization (β = −0.256, p = 0.005), indicating that higher levels of constructive social evaluation were associated with lower victimization experiences. Self-regulation was also a significant negative predictor (β = −0.311, p < 0.001), suggesting that adolescents with stronger self-regulatory inner dialogue reported fewer cyberbullying victimization experiences. Regarding family communication patterns, conversation orientation significantly and negatively predicted cyberbullying victimization (β = −0.298, p < 0.001), whereas conformity orientation significantly and positively predicted victimization experiences (β = 0.303, p < 0.001). These findings demonstrate that both personal cognitive processes and family communication dynamics contribute significantly to adolescents’ vulnerability to cyberbullying victimization.Conclusion: The findings indicate that inner self-talk and family communication patterns play substantial roles in understanding and predicting cyberbullying victimization among adolescents. Specifically, higher levels of self-regulation, constructive social assessment, and open family conversation are associated with reduced vulnerability to cyberbullying, whereas greater conformity-oriented family communication is linked to increased victimization risk.